Decontamination of Radioactive Material by Nd:YAG Laser - Won, Huijun; Park, Jungsoon; Jung, Chonghun; Choi, Wangkyu; Moon, Jeikwon (Asian Journal of Chemistry, 2013)
Metal ion removal characteristics of a Q-switched Nd:YAG laser on Type 304 stainless steel were investigated by varying the shot numbers under three wavelength conditions at 12.0 J/cm2. It was found that Cs+ ions and Co2+ ions were satisfactorily removed within 10 laser shots at 532 nm and at 355 nm. It was difficult to remove the metal ions on Type 304 stainless steel at 1064 nm. Decontamination characteristics of 4 kinds of materials artificially contaminated with Co60 and Cs137 were also investigated at 532 nm. Decontamination of the paint-coated surface was easy and the decontamination factors were over 1339 after two times' application of laser irradiation at 9.4 J/cm2. For type 304 stainless steel, inconel 600 and concrete specimens, decontamination factors were over 110 after two times' application of laser irradiation at 14.2 J/cm2. It was also found that Cs137 and Cs134 were easily ablated when the laser fluence is 14.2 J/cm2 during the 20 laser shots at 532 nm.